Protection of Private Rights to Copyright Portraits of Silhouette - Fajar Tri Septiono; Budi Hermono (Universitas Negeri Surabaya, 2024)
The portrait is copyrighted works protected by the Copyright Law. The problem raised in this study is that when a portrait is taken by a photographer, which is no visible face of the person being photographed. The purpose of this research is to analyze whether the object in the portrait but only in silhouette has a private right to copyright. The portrait to be studied is a portrait entitled